Physical activity health literacy in patients with chronic diseases: a concept analysis - Zhang, Xiaotian; Bi, Ruixue; Wang, Xinyu; Bu, Yuxuan; Liu, Xiaoping; Liu, Yu; Cui, Ruihong; Wang, Yankang; Li, Hongyan (Frontiers in Public Health, 2025)
AimsPhysical activity health literacy plays a positive role in optimizing individuals' physical activity health behaviors and is one of the key abilities for achieving proactive health management. This study is to clarify the concept of physical activity health literacy in patients with chronic diseases.MethodsThe Rodgers' evolutionary method of concept analysis was used to identify the antecedents, attributes, and consequences of the concept of “physical activity health literacy” in patients with chronic diseases.ResultsThree critical attributes were identified: functional, communicative, and critical physical activity literacy. Antecedents were classified into three categories: disease, cognitive, and social-psychological factors. The consequences include three themes: improving disease symptoms, improving quality of life, and promoting social-psychological health.ConclusionThe findings of this concept analysis contribute to a deeper understanding and clarification of physical activity health literacy.